Diversity of Trichoderma species associated with green mold contaminating substrates of Lentinula edodes and their interaction - Cao, Zi-Jian; Zhao, Juan; Liu, Yu; Wang, Shou-Xian; Zheng, Su-Yue; Qin, Wen-Tao (Frontiers in Microbiology, 2024)
The contamination of Trichoderma species causing green mold in substrates poses a significant obstacle to the global production of Lentinula edodes, adversely impacting both yield and quality of fruiting bodies. However, the diversity of Trichoderma species in the contaminated substrates of L. edodes (CSL) in China is not clear. A total of 150 samples were collected from four provinces of China during a two-year-investigation to assess the biodiversity of Trichoderma in the CSL. A total of 90 isolates were obtained and identified as 14 Trichoderma species, including six new species named as Trichoderma caespitosus, T. macrochlamydospora, T. notatum, T. pingquanense, T. subvermifimicola and T. tongzhouense. Among which, T. atroviride, T. macrochlamydospora and T. subvermifimicola were the dominant species in the CSL. Meanwhile, three known species, T. auriculariae, T. paraviridescens and T. subviride, were isolated from the CSL for the first time. Their phylogenetic positions were determined by sequence analyses of the combined partial sequences of translation elongation factor 1-alpha and the second largest RNA polymerase subunit encoding genes. Morphological distinctions between the new species and their close relatives were noted and discussed. In addition, resistance of L. edodes to the dominant Trichoderma species were evaluated in vitro, and results showed that strains of L. edodes generally had poor resistance to Trichoderma contamination with L. edodes strain SX8 relatively higher resistant.